2021
DOI: 10.3390/catal11060675
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Photocatalytic Materials for Urban NOx Remediation

Abstract: NOx is a pervasive pollutant in urban environments. This review assesses the current state of the art of photocatalytic oxidation materials, designed for the abatement of nitrogen oxides (NOx) in the urban environment, and typically, but not exclusively based on titanium dioxide (TiO2). Field trials with existing commercial materials, such as paints, asphalt and concrete, in a range of environments including street canyons, car parks, tunnels, highways and open streets, are considered in-depth. Lab studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 139 publications
(368 reference statements)
0
14
0
Order By: Relevance
“…PCCs have gained significant attention for NOx abatement in urban environments, though there is debate over their effectiveness (sources vary wildly, but it is likely <2% reduction). 207 The coatings used vary in the use of suspension medium, porosity, and roughness that the actual effectiveness of the PC is obscured. What does stay consistent is the choice of commercial P25-degussa, a now lower performing photocatalyst in a rapidly evolving field.…”
Section: Treatment and Reusementioning
confidence: 99%
“…PCCs have gained significant attention for NOx abatement in urban environments, though there is debate over their effectiveness (sources vary wildly, but it is likely <2% reduction). 207 The coatings used vary in the use of suspension medium, porosity, and roughness that the actual effectiveness of the PC is obscured. What does stay consistent is the choice of commercial P25-degussa, a now lower performing photocatalyst in a rapidly evolving field.…”
Section: Treatment and Reusementioning
confidence: 99%
“…It should be noted that for oxidizing photocatalysts, NO 3 – remains bound to the surface, which can inhibit their activity, and therefore typically requires rainfall or washing to restore their activity . A range of building materials have been incorporated with such photocatalysts to remedy NO x pollution, including paints, concretes, asphalts, and tiles for streets, walls, and tunnels. ,,, Nevertheless, what has been less well studied to date is the activity of photocatalytic coatings on low-surface-area glass substrates, where a commercial photocatalytic coating for general-purpose self-cleaning shows nominal activity toward NO gas …”
Section: Introductionmentioning
confidence: 99%
“…In their study [ 8 ], the degradation of NO during photocatalytic oxidation was measured using photocatalytic coatings applied to mortars and glass substrates. The impact of physical parameters on the efficiency of NO x removal has been widely analyzed [ 29 ] using different test setups [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, NO x oxidation can lead to the formation of various by-products other than NO 2 , such as ozone (O 3 ) [ 29 ]. It has been observed that ozone formation is facilitated by high concentrations of airborne pollutants along with nitrogen oxides in natural conditions.…”
Section: Introductionmentioning
confidence: 99%